2020
DOI: 10.1038/s41598-020-73216-8
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effects of the Atypical Dissociative Hallucinogen Salvinorin A on Functional Connectivity in the Human Brain

Abstract: Salvinorin A (SA) is a κ-opioid receptor agonist and atypical dissociative hallucinogen found in Salvia divinorum. Despite the resurgence of hallucinogen studies, the effects of κ-opioid agonists on human brain function are not well-understood. This placebo-controlled, within-subject study used functional magnetic resonance imaging for the first time to explore the effects of inhaled SA on strength, variability, and entropy of functional connectivity (static, dynamic, and entropic functional connectivity, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 62 publications
2
36
2
Order By: Relevance
“…Although we do not see a persistent effect on DMN connectivity, acute disruption of the DMN may still be therapeutically relevant (Carhart-Harris and Friston, 2019;Mason et al, 2020). Intake of both Salvinorin-A, a 5-HT2AR-independent hallucinogen, and MDMA, which has a subjective effect profile distinct from serotonergic psychedelics (Doss et al, 2020;Müller et al, 2020;Roseman et al, 2014), leads to a reduction in DMN connectivity. Reduced DMN connectivity is not associated with ego-dissolution in response to psilocybin (Lebedev et al, 2015).…”
Section: Additional Effects On Connectivitycontrasting
confidence: 53%
“…Although we do not see a persistent effect on DMN connectivity, acute disruption of the DMN may still be therapeutically relevant (Carhart-Harris and Friston, 2019;Mason et al, 2020). Intake of both Salvinorin-A, a 5-HT2AR-independent hallucinogen, and MDMA, which has a subjective effect profile distinct from serotonergic psychedelics (Doss et al, 2020;Müller et al, 2020;Roseman et al, 2014), leads to a reduction in DMN connectivity. Reduced DMN connectivity is not associated with ego-dissolution in response to psilocybin (Lebedev et al, 2015).…”
Section: Additional Effects On Connectivitycontrasting
confidence: 53%
“…Alternatively, similarities may be owing to converging downstream mechanisms, such as default-mode network (DMN) disintegration (e.g., Winkelman, 2017 ), considered the gross neural correlate of psychedelic action by 5HT-2A agonism. For example, salvia divinorum , a Mexican shamanic herb and atypical psychedelic generative of disconnection of consciousness to immersive spaces, though stimulating the kappa-opioid receptor it similarly reduces static functional connectivity in the DMN ( Doss et al, 2020 ). Neurophysiologically, such radical perceptual restructuring and ‘world building’ may be owing to collapse of alpha-beta wave, and dominance of delta-theta wave ( Timmermann et al, 2019 ; Pallavicini et al, 2020 ) and forward travelling wave activity across the cortex ( Alamia et al, 2020 ; Gallimore, 2020 ), evidenced at least by DMT.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, acute subjective effects induced by other hallucinogenic drugs with weak or no affinity for 5-HT2A receptors (e. g., ketamine, salvinorin A, ibogaine) share some similarities with those induced by classical psychedelics. It has recently been shown that, in particular, changes in subjective experience and brain connectivity evoked by savinorin A (a kappa opioid receptor) resemble those induced by LSD or psilocybin, highlighting a potential involvement of the opioid receptor system [94,95].…”
Section: Monoamine Systems and Receptorsmentioning
confidence: 99%